ARTIFICIAL INTELLIGENCE AND THE IMPORTANCE OF MULTIMEDIA TECHNOLOGIES IN EDUCATION - Haqberdiyev Bahrom Bobonazarovich (Ecomind Press, 2026)
This article elucidates the role and potential of artificial intelligence (AI) and multimedia technologies in the modern education system, as well as the issues of increasing educational efficiency through their integration. The possibilities for organizing individualized education based on AI, automating the teaching process, and data analysis are examined. Furthermore, the application of multimedia technologies in the educational process, their didactic advantages, and practical significance are highlighted. The article also outlines existing problems in implementing these technologies and proposes solutions to overcome them.
Keywords: Artificial intelligence, multimedia technologies, digital education, interactive teaching, individualized learning, information technology.